Overexpression of Hexokinase 2 is epigenetically regulated by frequent hypomethylation in glioblastoma multiforme. (31st January 2018) - Blakeway, Daniel; Karakoula, Katherine; Morris, Mark; Rowther, Farjana; Eagles, Lawrence; Darling, John; Warr, Tracy
Abstract: HK2 has a prominent role in glycolysis, acting as the rate-limiting step in the pathway. HK2 is highly expressed in many cancers, with overexpression associated with drug resistant phenotypes. In parallel, its inhibition has improved the effectiveness of anticancer agents. Evidence indicates that HK2 is epigenetically silenced in normal tissue, and hypomethylation is the driving factor of increased expression in tumours, suggesting HK2 as a potential genetic modifier and therapeutic target. This study determines the role of methylation and its association with expression levels of HK2 in glioblastoma multiforme (GBM) fresh frozen biopsies and patient-derived GBM short-term cultures, by pyrosequencing and quantitative PCR. Anti-proliferative effects of HK2 inhibitors and their mechanism of action was investigated by cytotoxicity assays and FACS analysis. Hypomethylation was seen in all GBM biopsies(n=85) compared to normal brain tissue; average methylation of 4.6% compared to 26% respectively (p< 0.0001). Hypomethylation was also in all culture samples(n=9). An increase in HK2 expression was detected, ranging between 6 to >1000fold change in GBM biopsies(n=50) and 30 to >1000 in cultures(n=10), compared to normal brain tissue. There was a strong correlation between methylation and level of expression (p< 0.0001) as biopsies with HK2 expression greater than the mean fold change additionally displayed hypomethylation levels below <3% methylation. The anti-proliferative effects of the HK2 inhibitor bromopyruvic acid (BPA) were determined in GBM cultures(n=12). BPA induced anti-proliferative effects and increased apoptotic levels in cultures. Elevated expression of HK2 (>mean fold change) was associated with greater sensitivity to BPA. Significantly higher levels of apoptosis were induced after treatment with BPA at ID50 in cultures expressing high HK2 (>mean fold change) (p< 0.0014). This study establishes a strong correlation between hypomethylation and increased expression of HK2. Furthermore, demonstrating the potential of HK2 inhibitors as a novel therapy in a significant subset of GBM.